PhysioAR: An augmented reality system applied in respiratory physiotherapy for hypertensive patients - Silva, Matheus V. da; Pacagnelli, Francis L.; Almeida, Leandro L. de; Siscoutto, Robson A. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide. Approximately 1.13 billion people suffer from arterial hypertension (AH), a condition that stands out among all other CVD risk factors. One of the main non-pharmacological treatments for AH is the performance of physical activities. Studies have also demonstrated the possibility of blood pressure control through the application of breathing exercises. Such exercises can be performed even at home. Due to the limitations concerning physical exercise for patients with uncontrolled hypertension, clinicians often have their patients conduct breathing exercises before a physiotherapy session for blood pressure reduction purposes. However, more tools are needed to assist clinicians with this approach. Considering these circumstances, this paper introduces PhysioAR, an augmented reality system designed to assist in respiratory therapy treatments for hypertensive patients. Using three-dimensional virtual environments and specific hardware for vital sign measurements, PhysioAR enables the creation and application of respiratory therapy sessions by a physiotherapist professional. At the end of its development, a group of usability experts evaluated the system through a questionnaire based on Nielsen's heuristic evaluation of user interfaces. After evaluation, PhysioAR obtained an average performance of 4.3 by the Likert scale. All evaluators agreed that using the system was a pleasant experience, which suggests that PhysioAR has potential for physiotherapy clinics. The questionnaire application exposed some user experience problems. This demonstrated the effectiveness of a questionnaire-based evaluation to identify possible system problems.